Dynamics and Macroeconomic Interaction of Government Expenditure in BELL and PIIGS: A Comparative Analysis - Velichkov, Nikolay (Research Papers, 2021)
The paper looks at the dynamics of government expenditure in the BELL (Bulgaria, Estonia, Latvia and Lithuania) and PIIGS (Portugal, Ireland, Italy, Greece and Spain) countries for the period 2000-2019, emphasizing its relationship with changes in macroeconomic activity. The empirical results show clear peculiarities both in time and in relation to the two distinct groups of countries. These differences between the BELL and PIIGS countries are reflected both in the own government expenditure dynamics and in the share of GDP, as well as in the cyclical interaction of government spending.
Keywords: Public expenditures; Macroeconomic activity; BELL countries; PIIGS countries